Stoking the Fire: How Dying Cells Propagate Inflammatory Signalling through Extracellular Vesicle Trafficking - Baxter, Amy A. (Int J Mol Sci, 2020)
Communication between dying cells and their environment is a critical process that promotes tissue homeostasis during normal cellular turnover, whilst during disease settings, it can contribute to inflammation through the release of intracellular factors. Extracellular vesicles (EVs) are a heterogeneous class of membrane-bound cell-derived structures that can engage in intercellular communication via the trafficking of bioactive molecules between cells and tissues. In addition to the well-described functions of EVs derived from living cells, the ability of dying cells to release EVs capable of mediating functions on target cells or tissues is also of significant interest. In particular, during inflammatory settings such as acute tissue injury, infection and autoimmunity, the EV-mediated transfer of proinflammatory cargo from dying cells is an important process that can elicit profound proinflammatory effects in recipient cells and tissues. Furthermore, the biogenesis of EVs via unique cell-death-associated pathways has also been recently described, highlighting an emerging niche in EV biology. This review outlines the mechanisms and functions of dying-cell-derived EVs and their ability to drive inflammation during various modes of cell death, whilst reflecting on the challenges and knowledge gaps in investigating this subgenre of extracellular vesicles research.